PENERAPAN STRATEGI PEMBELAJARAN MATEMATIKA SMALL-GROUP WORK DENGAN MENGGUNAKAN LEMBAR KERJA SISWA PADA KELAS X DI SMKN 2 PADANG PANJANG - lis, Yurna (FKIP UMSB, 2017)
Based on the daily tests of pure mathematics odd semester students of class X SMK Negeri 2 Padang Panjang is known that the students' mathematics learning is still low. Based on observations, the learning process is still centered on the teacher. The level of students' understanding of the material being taught is still lacking. Students participate less actively in the learning process, not take the initiative to learn about their own material to be covered. One effort that strategy is expected to increase the activity of students is to apply mathematics learning strategy Small-Group Work using students' worksheets. The problems of this study is whether the small group strategy implementation work using student worksheets can increase the activity of students and student learning outcomes. This type of research is experimental research, the design of Randomized Control Group Only Design. The population in this study were all students of class X SMK Negeri 2 Padang Panjang registered in the Academic Year 2015/2016. Samples were taken at random, and was elected class X TKJ 1 as an experimental class, and a class X TKJ 2 as the control class. Collecting data in research using achievement test in the form of essay test as many as eight items and observation sheet to see student activity. The conclusion of this study is the student activity in the learning of mathematics Small-Group Work tends to increase with the use of worksheets in the learning process at every meeting and obtained and then which means that rejected. That is the result of students 'mathematics learning by using mathematical learning strategies Small-Group Work using student worksheets better than not using mathematics learning strategy Small-Group Work using students' worksheets. Kata Kunci: Strategi Small-Group Work, lembar kerja siswa, pembelajaran matematika, aktivitas siswa dan hasil belajar.